Trafficking of the exported P. falciparum chaperone PfHsp70x - Rhiel, Manuel; Lanzer, Michael; Sanchez, Cecilia P. (Scientific reports, 2016)
Plasmodium falciparum extensively modifies its chosen host cell, the mature human erythrocyte. This remodelling is carried out by parasite-encoded proteins that are exported into the host cell. To gain access to the human red blood cell, these proteins must cross the parasitophorous vacuole, a membrane bound compartment surrounding the parasite that is generated during the invasion process. Many exported proteins carry a so-called PEXEL/HT signal that directs their transport. We recently reported the unexpected finding of a species-restricted parasite-encoded Hsp70, termed PfHsp70x, which is exported into the host erythrocyte cytosol. PfHsp70x lacks a classical PEXEL/HT motif, and its transport appears to be mediated by a 7 amino acid motif directly following the hydrophobic N-terminal secretory signal. In this report, we analyse this short targeting sequence in detail. Surprisingly, both a reversed and scrambled version of the motif retained the capacity to confer protein export. Site directed mutagenesis of glutamate residues within this region leads to a block of protein trafficking within the lumen of the PV. In contrast to PEXEL-containing proteins, the targeting signal is not cleaved, but appears to be acetylated. Furthermore we show that, like other exported proteins, trafficking of PfHsp70x requires the vacuolar translocon, PTEX.
Gesehen am 21.10.2021